Oil pollution in the baltic sea - Lavrova, Olga Yu; Kostianoy, Andrey G. (The Handbook of Environmental Chemistry, 2014)
This thorough review is based on observational satellite, airborne and in-situ data, scientific literature and technical reports, as well as the substantial experience of the authors, who hail from several Baltic Sea countries. They pay special attention to national practices, HELCOM and EMSA CleanSeaNet activities in oil pollution monitoring, and show different applications of the Seatrack Web model for oil spill drift prediction and the identification of illegal polluters, as well as for environmental risk assessment. Furthermore, some of the results on satellite monitoring of the Nord Stream gas pipeline construction in the Gulf of Finland are presented.  This volume addresses the needs of specialists working in different fields of marine, environmental, and remote sensing sciences. It is a useful handbook on oil pollution for international and governmental agencies, as well as for policy makers who plan and manage oil and gas projects, the construction of ports and terminals, shipping, fishery, recreation, and tourist activities in the Baltic Sea. It also offers graduate and undergraduate students in marine and environmental sciences a valuable resource and reference work on the subject.